Presynaptic BDNF-TrkB signaling contributes to mechanical allodynia in a mouse model of chronic neuropathic pain - Ding, Ting; Zhang, Lanying; Xu, Jingqing; Liu, Maomao; Ou-Yang, Yao; Liu, Sheng (Brain research bulletin, 2025)
In the spinal cord, brain-derived neurotrophic factor (BDNF) exerts its regulatory role on neuropathic pain through its receptor TrkB. This study constructed a conditional TrkB gene knockout mouse model, targeting all nociceptive neurons (SNSCre;TrkBfl/fl) or all sensory neurons (AdvillinCre;TrkBfl/fl) in the dorsal root ganglia (DRG), to investigate the function of presynaptic BDNF-TrkB signaling in the dorsal horn and its impact on specific sensory modalities. In situ hybridization (ISH) was used to detect TrkB expression in nociceptive SNStdTomato neurons, revealing that TrkB is expressed in both sensory neurons and nociceptors in the DRG. Triple immunofluorescence techniques were employed to detect the co-expression of neuron-specific markers NF200, CGRP, and IB4 with TrkB mRNA, and the co-expression ratios were analyzed. To assess motor function and aversive behavior, CatWalk (CW), home cage (HC), and wheel rotation (WR) tests were conducted; basic pain and touch sensitivity were evaluated using von Frey, cotton swabs, brush, pinprick, acetone, cold plate, Hargreaves, and hot plate tests, as well as tapping and hair clamp tests, with no effects observed on neurodevelopment, motor function, or aversive behavior. In addition, this study used the CCI model to conduct behavioral tests related to nerve injury in SNSCre;TrkBfl/fl and AdvillinCre;TrkBfl/fl mice. After CCI surgery, both mouse strains exhibited severe dynamic and punctate mechanical allodynia deficits, while thermal and cold allodynia developed normally. Ultimately, by administering exogenous BDNF via intrathecal (IT) injection, mechanical allodynia deficits were observed in AdvillinCre;TrkBfl/fl and SNSCre;TrkBfl/fl mice. The results confirmed that TrkB is expressed presynaptically and plays a role in the development of dynamic and punctate mechanical allodynia during BDNF-induced spinal plasticity responses, but has no effect on thermal or cold allodynia. In conjunction with previous studies, these findings suggest that BDNF may partially regulate presynaptic inhibition following nerve injury through TrkB.
Online verfügbar: 7. November 2025, Artikelversion: 24. November 2025
Gesehen am 25.02.2026